Tropical vegetables and their genetic resources - Grubben, G.J.H.; Tindall, H.D.; Williams, J.T.; International Board for Plant Genetic Resources (1977)
Plant breeding, germplasm conservation and germplasm research in tropical zones and subtropical zones; plant production and consumption of vegetables in Latin America, Africa and Asia; specific reference is made to fruit vegetables, leafy vegetables, cucurbits, allium and brassicas; including a list of agricultural institutions dealing with vegetable germplasm resources.